Extract gold from electronic waste using chemical leaching - Ahmad Shakir Ikhwan Ahmad Kamaruddin (2024)
The fast-growing electronic waste (e-waste) produced worldwide presents environmental challenges and opportunities for resource recovery. Among the valuable components of e-waste, gold stands out for its high economic value and unique properties. This study explores the feasibility and efficiency of extracting gold from electronic waste through chemical soluble. Chemical leaching involves the use of reagents to dissolve and recover gold from electronic components. The research uses a systematic experimental design to investigate the influence of various parameters, such as identifying the type of gold and how much gold is in the components. Hydrochloric acid is considered a leaching agent. Characterization techniques such as the Acid Aqua Regia test, Fluorescent X-ray scan (XRF) and Magnetic test are used to analyze electronic waste samples and monitor compositional changes during the leaching process. The economic viability of the proposed method is also assessed by comparing it with traditional gold extraction methods. The research has obtained a gold yield of 1.5 grams and a purity of 23K gold. Preliminary results indicate promising gold recovery rates using chemical leaching, providing a sustainable and economically viable alternative for e-waste recycling. The findings of this study contribute to the development of environmentally friendly methods for recovering valuable metals from electronic waste, thereby addressing both environmental concerns and the growing demand for precious metals in various industries. The insights gained from this research have the potential to pave the way for scalable and sustainable processes in the recycling of electronic waste.